The Progressive Reduction of Cholesterol: Does it Open a Way to Psychopathology? - Cocchi, Massimo (Progress in Nutrition, 2021)
The purpose of this commentary is to highlight the valuable role of Cholesterol in the biochemical dynamics of life. Some curious characteristics of the relationship between Cholesterol and Linoleic Acid are highlighted, not only, as widely documented in humans, but also in different animals such as, for example, bees. In summary, the excessive reduction of Cholesterol could have a disastrous impact on the predisposition to psychopathology, even in its most serious manifestations such as suicide.